Mulheres assistidas na atenção primária à saúde no contexto da menopausa, no município de Unaí-MG - Martins, Maria das Neves (Universidade do Vale do Rio dos Sinos, 2021)
This research, on the theme of menopause and health, aims to verify the demands, expectations and services provided by Primary Health Care (PHC) to women in the context of menopause in the city of Unaí-MG. The methodological approach was qualitative, based on a semi-structured interview. Twenty (20) women aged between 50 and 55 years, differentiated in their socioeconomic strata and educational level, were interviewed. The field research was carried out in June 2021. As a result of the Pandemic scenario by Covid-19, the interviews were carried out by telephone calls, recorded and transcribed for analysis. The discussion was built giving support to the analysis of the collected data, making it possible to demonstrate the complexity and subjectivity that accompanies the bodily changes arising from menopause. Regarding the service performed in a PHC, it was possible to identify women's demands for specialized care at this stage of life.
Keywords: Mulher; Corpo; Menopausa; Saúde; Ciências sociais; Woman; Body; Menopause; Health; Social science; ACCNPQ::Ciências Humanas::Sociologia